Aβ42 oligomers trigger synaptic loss through CAMKK2-AMPK-dependent effectors coordinating mitochondrial fission and mitophagy - Lee, Annie; Kondapalli, Chandana; Virga, Daniel M; Lewis, Tommy L; Koo, So Yeon; Ashok, Archana; Mairet-Coello, Georges; Herzig, Sebastien; Shaw, Reuben; Sproul, Andrew; Polleux, Franck (bioRxiv, 2019)
During the early stages of Alzheimer's disease (AD) in both mouse models and human patients, soluble forms of Amyloidβ1-42 oligomers (Aβ42o) trigger loss of excitatory synapses (synaptotoxicity) in cortical and hippocampal pyramidal neurons (PNs) prior to the formation of insoluble Aβ plaques. We observed a spatially restricted structural remodeling of mitochondria in the apical tufts of CA1 PNs dendrites in the hAPP(SWE,IND) transgenic AD mouse model (J20), corresponding to the dendritic domain receiving presynaptic inputs from the entorhinal cortex and where the earliest synaptic loss is detected in vivo. We also observed significant loss of mitochondrial biomass in human neurons derived from a new model of human ES cells where CRISPR-Cas9-mediated genome engineering was used to introduce the Swedish mutation bi-allelically (APP-SWE/SWE). Recent work uncovered that Aβ42o mediates synaptic loss by over-activating the CAMKK2-AMPK kinase dyad, and that AMPK is a central regulator of mitochondria homeostasis in non-neuronal cells. Here, we demonstrate that Aβ42o-dependent over-activation of CAMKK2-AMPK mediates synaptic loss through coordinated MFF-dependent mitochondrial fission and ULK2-dependent mitophagy in dendrites of PNs. We also found that the ability of Aβ42o-dependent mitochondrial remodeling to trigger synaptic loss requires the ability of AMPK to phosphorylate Tau on Serine 262. Our results uncover a unifying stress-response pathway triggered by Aβo and causally linking structural remodeling of dendritic mitochondria to synaptic loss.